Performance assessment in teacher education research—A scoping review of characteristics of assessment instruments in the DACH region - Albu, Carina; Lindmeier, Anke (Zeitschrift für Erziehungswissenschaft, 2023)
In recent years, a new branch of teacher competence research has emerged in which competence is measured close to teaching performance. Such so-called performance assessment approaches are gaining increasing attention, but the research field is still fragmented. A lack of overview and varying reporting practices interfere with its coherent development. This scoping literature review provides an overview of recent advances and the current state of performance assessment instruments in teacher education research in German-speaking countries. We examined assessment instruments that provide objective, standardised measurement procedures based on observable behaviour regarding teaching demands. Based on 20 assessment instruments, a category system with 14 categories was inductively developed, capturing their characteristics in terms of context, test methods, and alignment with criteria for performance assessment. Despite the considerable variation, three types of teacher performance assessment instruments could be identified through qualitative and exploratory statistical analyses. The results show continuity as well as development compared to previous reviews and provide suggestions on advancing the still-emerging research field. For example, they can be used to foster the coherence of the research field by providing information on typical instrument differences and similarities as well as essential reporting demand
CRIS-Team Scopus Importer:2024-10-02
Keywords: Teacher education; Performance assessment; Situated testing; Review; Instrument design

What difference does teacher knowledge make? A feasibility study on using elements of comprehension as indicators for school-related content knowledge - Albu, Carina; Lindmeier, Anke (Proceedings of the International Group for the Psychology of Mathematics Education, 2023)
It is assumed that school-related content knowledge, as knowledge about connections between academic and school mathematics, is necessary for high-quality mathematics teaching at secondary level. Nevertheless, research on how teachers use this knowledge in action is lacking. In this study, we investigate the use of elements of comprehension (EoCs) as an indicator of school-related content knowledge in teaching situations. As part of a feasibility study, we analyzed video sequences of three pre-service mathematics teachers in short teaching simulations on the concept of limits of sequences. The occurrence of EoCs could be coded intersubjectively reliable, and the observations were in line with the participants’ knowledge assessed prior to the study. We discuss the further potential of the approach for research on teacher knowledge.
CRIS-Team Scopus Importer:2024-10-02